NIFTy galaxy cluster simulations – VI. The dynamical imprint of substructure on gaseous cluster outskirts. Issue 3 (14th November 2019) - Power, C; Elahi, P J; Welker, C; Knebe, A; Pearce, F R; Yepes, G; Davé, R; Kay, S T; McCarthy, I G; Puchwein, E; Borgani, S; Cunnama, D; et al.
ABSTRACT: Galaxy cluster outskirts mark the transition region from the mildly non-linear cosmic web to the highly non-linear, virialized, cluster interior. It is in this transition region that the intracluster medium (ICM) begins to influence the properties of accreting galaxies and groups, as ram pressure impacts a galaxy's cold gas content and subsequent star formation rate. Conversely, the thermodynamical properties of the ICM in this transition region should also feel the influence of accreting substructure (i.e. galaxies and groups), whose passage can drive shocks. In this paper, we use a suite of cosmological hydrodynamical zoom simulations of a single galaxy cluster, drawn from the nIFTy comparison project, to study how the dynamics of substructure accreted from the cosmic web influence the thermodynamical properties of the ICM in the cluster's outskirts. We demonstrate how features evident in radial profiles of the ICM (e.g. gas density and temperature) can be linked to strong shocks, transient and short-lived in nature, driven by the passage of substructure. The range of astrophysical codes and galaxy formation models in our comparison are broadly consistent in their predictions (e.g. agreeing when and where shocks occur, but differing in how strong shocks will be); this is as we would expect of a process driven by large-scale gravitational dynamics and strong, inefficiently radiating, shocks. This suggests that mapping such shock structures in the ICM in a cluster's outskirts (via e.g. radio synchrotron emission) could provide a complementary measure of its recent merger and accretion history.